Potential of Inhibitors for Increasing Response of Lowland Rice to Urea Fertilization - Buresh, R.J.; De Datta, S.K.; Padilla, J.L.; Chua, T.T. (Wiley, 1988)
The full potential of biological inhibitors to increase the yield response of lowland rice (Oryza sativa L.) to urea fertilization has remained uncertain, because no chemical has been available to completely eliminate all gaseous loss of applied urea‐N. Two field 15N balance studies at multiple rates of urea with and without a urease inhibitor, phenyl phosphorodiamidate, were conducted in the Philippines. The urea was split broadcast into floodwater at 16 or 18 d after transplanting and at 5 to 10 d after panicle initiation. The applied urea‐15N not recovered in the rice and soil at crop maturity was assumed to represent total gaseous N loss and hence the potential savings in urea‐N that could be obtained with the use of an inhibitor that completely eliminated gaseous N loss. The potential savings in urea‐N consistently increased with increasing N rate. In 1985. the potential urea‐N savings were 17, 23, and 29% at 30, 60, and 120 kg N ha−1, respectively. In 1986, they were 13, 34, and 37% at 40,80, and 120 kg N ha−1, respectively. In each experiment, there was a significant quadratic response in grain yield to applied N. Models were developed for observed responses to applied urea and for potential yield responses to urea assuming complete elimination of gaseous N loss with no effect on rice other than increasing the availability of fertilizer‐N. Elimination of gaseous N loss could have increased grain yield by a maximum of 6 and 8% in 1985 and 1986. respectively. These percentages corresponded to 0.4 and 0.5 Mg ha−1 increases in grain yield, respectively.